Potentiality of native Bacillus species in enhancing sesame seed germination and their antagonism against Macrophomina phaseolina under in vitro conditions: POTENTIALITY OF NATIVE BACILLUS SPP. AGAINST MACROPHOMINA PHASEOLINA - P KISHORE VARMA; C YAMUNA; V SURESH; M RAVI TEJA; K VIJAY KRISHNA KUMAR (Journal of Oilseeds Research, 2017)
Native Bacillus species screened fromrhizosphere ofsesame (Sesamum indicum L.) were tested for their growth promoting and antagonistic effects. Based on 16S rRNA gene sequence based homology, the bacterial isolates were identified as B. amyloliquefaciens, B. aryabhattai, B. cereus, B. flexus, B. megaterium, B. methylotrophicus, B. pumilus and B. subtilis. Results on biochemical characterization of Bacillus species indicated that majority of the isolates were producing catalase and were found to be diazotrophs. Only few isolates were found to produce protease, cellulase and HCN. Onlyone isolate (B. amyloliquefaciens)was found to be phosphate solubilizer. Further, in vitro antagonistic assay revealed that Bacillus subtilis and B. methylotrophicus could inhibit the mycelial growth of M. phaseolina by 30.9 and 29.0 per cent, respectively. Majority of the Bacillus species tested have increased sesame seed germination, radicle and plumule length compared to control. Overall, our results suggested the scope and potentiality of Bacillus species in promoting sesame seed germination and growth promotion besides suppression of pathogen.